Displacement Control Of Piezoelectric Patch Actuator Using PID Controller - Maslan, Mohd Nazmin; Jamaludin, Zamberi; A Rahman, Muhamad Arfauz; Chiew, Tsung Heng; Md Solihin, Mohd Zaidi; Karjanto, Juffrizal; Musa, Mailah (Publications International, 2014)
The piezoelectric actuator is an electromechanical device which can transduce energy between electrical and mechanical. Usually it is used for managing extremely small displacements up to micro range. Due to piezoelectric actuator have characteristic of high stiffness, simplicity, fast response, and low wear and tear, it is widely used nowadays in industries such as electrical engineering applications and high precision mechanical system. However, piezoelectric has the disadvantages in terms of its dielectric material properties and hysteretic behaviour inherent causing inaccuracy behaviour to maintain the output displacement. To overcome this problem a PID controller is designed to regulate the output displacement and minimize the system error. The parameters are selected by using SISO Tool method. In this paper, PID controller design methods of piezoelectric actuator were presented to control the output displacement thus obtaining a stable and efficient system. Simulation and experimental test were conducted to verify of the proposed controller.